The Reality of Social Responsibility in Algerian Family Companies - Case Study of ETMA Company in Saida Province - AZZOUZ, Amina; GHRISSI, Larbi; RAHMANI, Mira Karima (Journal of Finance & Corporate Governance, 2019)
This study aims to reflect the conception of the social responsibility with all its dimensions towards the stakeholders in the Algerian companies, in order to achieve this, we set up the family business ETMA-Saida where we conducted an interview with the director. The purpose of this interview was to determine the vision of the concept of social responsibility as it is the primary manager and decision-maker in the company, the interview allowed us to know his managerial reasoning and to know whether he is rational or emotional based on intuition.